2017
DOI: 10.1371/journal.pone.0176844
|View full text |Cite
|
Sign up to set email alerts
|

LSL-KrasG12D; LSL-Trp53R172H/+; Ink4flox/+; Ptf1/p48-Cre mice are an applicable model for locally invasive and metastatic pancreatic cancer

Abstract: Pancreatic cancer (PC) accumulates multiple genetic mutations, including activating KRAS mutations and inactivating TP53, SMAD4 and CDKN2A mutations, during progression. The combination of mutant KRAS with a single inactivating TP53, SMAD4 or CDKN2A mutation in genetically engineered mouse models (GEMMs) showed that these mutations exert different synergistic effects in PC. However, the effect of the combination of TP53, CDKN2A and KRAS mutations on the trajectory of PC progression is unknown. Here, we report … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 42 publications
1
17
0
Order By: Relevance
“…This finding suggests that the growth and maintenance of basal microvilli might rely on blood flow. We also discovered basal microvilli in KRAS ‐mutated autochthonous pancreatic cancers of mice but not in orthotopic pancreatic cancers of mice [11,12,29]. However, the sizes of these tumors in mice are far smaller than those in human cancers.…”
Section: Discussionmentioning
confidence: 99%
“…This finding suggests that the growth and maintenance of basal microvilli might rely on blood flow. We also discovered basal microvilli in KRAS ‐mutated autochthonous pancreatic cancers of mice but not in orthotopic pancreatic cancers of mice [11,12,29]. However, the sizes of these tumors in mice are far smaller than those in human cancers.…”
Section: Discussionmentioning
confidence: 99%
“…To see if the microvasculature in the PCs of KIC presents basal microvilli, we have stained the PCs of KIC with a CD34 antibody. Similar to the microvasculature of human pancreatic cancers, autochthonous KPC, and KPIC tumors, 11,23 the microvasculature in KIC tumors also presents basal microvilli (Figure 2A). Consistent with the characteristics of human basal microvilli microvasculature, 11 we observed that the basal microvilli microvasculature in both KPC and KIC tumors has a lower level of VEGFR2 and pVEGFR2 (Y966) when compared to the microvessels in the near‐normal tissue (Figure 2B,C; Figure ).…”
Section: Resultsmentioning
confidence: 73%
“…Basal microvilli microvasculature exists in murine autochthonous PCs that harbor the KRAS mutation but not xenograft or orthotopic tumors 11,23 . These findings provide us with a limited tool to study the nutrient trafficking and blood flow of basal microvilli microvessels in PCs.…”
Section: Introductionmentioning
confidence: 89%
“…[92, 93, 94, 95, 96, 97, 98] Recent study shows that LSL-KrasG12D; LSL-Trp53R172H/+; Ink4flox/+; Ptf1/p48-Cre mouse model with multiple mutations is a more applicable model for preclinical investigation of locally invasive and metastatic pancreatic cancer. [99] The activated KRAS together with other gene mutations in pancreatic cells promotes PanINs to progress to invasive pancreatic cancers, making the models more relative to clinical pancreatic cancer. However, the GEMMs harbor same mutations in all pancreatic cells and they are homogeneous.…”
Section: Challenges In the Treatment Of Pancreatic Ductal Adenocarcinomamentioning
confidence: 99%